Kemampuan Mengelola Kelas Untuk Mengantisipasi Perilaku Bullying Melalui Model Manajemen Kelas Ramah Anak - Anisah, Anisah; Wulan, Sri; Hikmah, Hikmah (Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to determine the skills of PAUD teachers and prospective teachers in managing classes to anticipate bullying behavior in PAUD institutions through the implementation of the Child Friendly Class Management Model (MKRA). This research uses quantitative descriptive methods with survey techniques for PAUD teachers and classroom action research (PTK) for prospective PAUD teachers with data collection techniques using questionnaires, tests and observations. The sample in this study was 115 teachers who taught at non-formal PAUD institutions in Pulo Gadung District and 20 prospective teachers in the PG-PAUD FIP UNJ undergraduate study program. The research results show that teachers who have the ability to manage the classroom are in the quite good category at 60.80%. Meanwhile, the teacher's ability to anticipate child bullying in the classroom is 64.30%. These results illustrate that there are still many teachers who are unable to manage the classroom to anticipate children's bullying, which is characterized by the lack of teachers in recognizing the forms and characteristics of children's bullying, as well as the learning methods used. The results of classroom action research (PTK) show an increase in the ability of prospective teachers to manage the classroom from initial conditions of 50% to 70% in cycle 1 and 95% in cycle 2, which proves that the Child-Friendly Classroom Management Model (MKRA) can help improve competency managing classes for prospective PAUD teachers.